Análisis Financiero del “Consorcio Covilsa” de la Ciudad de Loja, Período 2014-2015. Propuesta de Mejoramiento - Angamarca Paccha, Katty Elizabeth (2017)
The thesis work was executed according to a general objective: TO PERFORM A FINANCIAL ANALYSIS OF THE "CONSORCIO COVILSA" OF THE CITY OF SHOP, PERIOD 2014-2015. PROPOSAL FOR IMPROVEMENT, in order to determine the economic and financial structure and complying with the requirements prior to choosing the Degree of Engineering in Accounting and Auditing, Public Accountant - Auditor, at the National University of Loja, thus conforming to the Regulation of Current Academic Regime. For the fulfillment of the first specific objective: "Analyzing the financial statements through the vertical and horizontal analysis to know the real financial - economic situation of the company with the application of this study was determined a growth in the year 2015 unlike 2014, Resulting in an increase of $ 78,753.26 in the Assets, equivalent to 9.78%; Liabilities have an increase of $ 102,788.28 representing 23.51% and equity has a decrease of $ -24,085.02 which is equivalent to -6.54%. Lugo's analysis and review of the Financial Statements applies the indicators that determine the liquidity, activity and profitability of the company. 5 Finally, the report of the Financial Analysis was carried out, where conclusions and recommendations are recorded, which will be used to make decisions, in order to inform the results of the Analysis of the Financial Statements for the years 2014 - 2015, the application Of a Financial Analysis to the consortium; So that it contains suggestions aimed at improving financial managem